2006
DOI: 10.1002/jgm.938
|View full text |Cite
|
Sign up to set email alerts
|

Naked Sendai virus vector lacking all of the envelope‐related genes: reduced cytopathogenicity and immunogenicity

Abstract: The deletion of genes from the SeV genome and the additional mutation are very effective for reducing both the immunogenic and cytopathic reactions to the SeV vector. These modifications are expected to improve the safety and broaden the range of clinical applications of this new class of cytoplasmic RNA vector.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
33
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
3
3
1

Relationship

1
6

Authors

Journals

citations
Cited by 38 publications
(35 citation statements)
references
References 26 publications
2
33
0
Order By: Relevance
“…18 rSeV/dFdMdHN is the further advanced design without any envelope-related genes in the vector genome. 19,20 These rSeVs were titrated by assessing CIU (cell infectivity units). [18][19][20] Role of SeV-envelope-related genes on host immune response S Tanaka et al The survival curves of these mice are also shown.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…18 rSeV/dFdMdHN is the further advanced design without any envelope-related genes in the vector genome. 19,20 These rSeVs were titrated by assessing CIU (cell infectivity units). [18][19][20] Role of SeV-envelope-related genes on host immune response S Tanaka et al The survival curves of these mice are also shown.…”
Section: Resultsmentioning
confidence: 99%
“…19,20 These rSeVs were titrated by assessing CIU (cell infectivity units). [18][19][20] Role of SeV-envelope-related genes on host immune response S Tanaka et al The survival curves of these mice are also shown. The curves were analyzed using Kaplan-Mayer's method.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…3 Using sophisticated manipulating technology of the genome of SeV, namely 'Reverse Genetics, ' we recently generated SeV vectors lacking envelope-related genes, including fusion (F) gene-deleted (SeV/DF), 4 matrix (M) gene-deleted (SeV/DM), 5 hemagglutinin/neuraminidase (HN) gene-deleted (SeV/DHN), both M and F genesdeleted (SeV/DMDF) 6 and all of the envelope-related genes-deleted (SeV/DMDFDHN). 7 Among the proteins contained in the viral lipid bilayer, M protein plays a central role in secondary virus assembly and budding from infected cells. Therefore, deletion of the M gene from SeV almost completely abolished virus maturation during formation of infectious particles in infected cells and instead caused cell-to-cell vector spreading through membrane fusion, forming large syncytia and resulting in cell death by the active F protein under supplementation of trypsin.…”
Section: Introductionmentioning
confidence: 99%